Creative heritage of V.I. Vernadsky and global challenges of sustainable development - Grachev, Vladimir (Advances in Social Sciences Research Journal, 2019)
The present article considers main aspects of creative heritage of V.I. Vernadsky in the sphere of global processes. It is shown that Vernadsky's theory of three main components of sustainable economic development (labor, capital, and creativity) is fundamental in the development of contemporary economy. The economic processes taking place in the present-day world are largely directed towards making a profit in the speculative turnover of capital, rather from using scientific and technological progress to meet the needs of people. The analysis of the interrelations of global problems of sustainable development in the economy, environment, and social sphere, allowed drawing the conclusion that the world could be destroyed by global fraud of speculative capital rather than by global warming. Based upon the latest report of the Club of Rome (2017), this path, disastrous for the modern world, has found understanding of the public. It is the aspiration for enrichment that creates some "global" problems. This is primarily related to the "global warming" problem. There is no such problem. There is a problem of global processes in the climate and the desire of economic elites to profit from this problem. The solution to global problems is associated with the noosphere balances and acceptable, equitable, and feasible conditions for sustainable development. The creative heritage of Vernadsky indicates the right way to address global challenges. This is creative thought, complementing the global natural balances based on homeostasis, and noospheric balances based on the world mind. Sustainable development embarks on a path of noosphere genesis, i.e. it is based on noospheric development, which is reasonable not only from the viewpoint of the mind of a single individual, but on the basis of the world mind and collective intelligence.